Comparing the metabolic profiles of raw and cooked pufferfish (Takifugu flavidus) meat by NMR assessment. (30th August 2019) - Yang, Luan; Dai, Bona; Ayed, Charfedinne; Liu, Yuan
Highlights: Metabolic profiles of pufferfish meat were firstly illuminated by NMR. The taste metabolites were in good agreement with sensory evaluation. The process effects on pufferfish taste were partly explained by their metabolites. Abstract: The difference of metabolite profiles between raw and cooked pufferfish (Takifugu flavidus) meat was explored by 1 H NMR technique and multivariate statistical methods. The orthogonal projection to latent structure-discriminant analysis (OPLS-DA) results showed an obvious separation between two samples. There were 24 dominating metabolites in the pufferfish muscle extraction, of which 11 metabolites changed significantly (p < 0.05), including 9 amino acids (alanine, leucine, methionine, tyrosine, glutamate, glycine, arginine, lysine, taurine), 1 organic acid (lactate) and 1 alkaloid (betaine). Moreover, the Student's t -test was performed to identify the different levels of metabolites. Sensory intensity experiments showed that there was a significant difference in the umami taste between raw and cooked pufferfish meat (p < 0.05). The content of glutamate, aspartate and 5′-IMP in the cooked meat increased, making the umami taste more intense. This study provided essential information about the metabolites explaining the taste difference between raw and cooked pufferfish meat.